Geochemistry of Neoproterozoic limestones of the Shahabad Formation, Bhima Basin, Karnataka, Southern India - Nagarajan, Ramasamy; Madhavaraju, J.; Armstrong-Altrin, J.; Nagendra, R. (The Association of Korean Geoscience Societies and Springer, 2011)
Major, trace and rare earth element (REE) geochemistry of carbonate rocks of the Neoproterozoic Shahabad Formation, Southern India were studied in order to investigate the depositional environment and source for the REEs. The PAAS (Post Archaean Australian Shale) normalized REE + Y pattern of Shahabad limestones have consistent seawater-like pattern i.e., i) LREE depletion (average (Nd/Yb)SN = 0.64 ± 0.08), ii) negative Ce anomaly, iii) positive Gd anomaly (average GdSN/Gd* = 1.05 ± 0.16), iv) superchondritic Y/Ho ratio (average Y/Ho = 38.13 ± 21.35). The depletion of LREE and enrichment of HREE are clearly indicated by the (La/Yb)SN, (Dy/Yb)SN and (Nd/Yb)SN ratios, which suggest the retention of seawater characteristics in these limestones. The negative Ce anomaly reflects the incorporation of REE directly from seawater or from the pore water under oxic condition, and also reveals the mixing of two-component systems with terrigenous clay (detrital) in the marine sediments. The terrigenous input in these limestones is confirmed by positive correlation of ΣREE with Al2O3, negative correlation of ΣREE with CaO and differences in Y/Ho ratios. V, Cr, and Sc, are positively correlated with Ti, and strong positive correlation of ΣREE with Fe2O3, Ni, Cr, Sc, and Y also indicate the presence of terrigenous materials in the Shahabad limestones.